PENDEKATAN PEMBELAJARAN BOLA VOLI DENGAN POLA TERMINAL TEACHING PADA SISWA KELAS IV SD NEGERI NGALIYAN 03 KECAMATAN NGALIYAN KOTA SEMARANG TAHUN AJARAN 2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study aims to determine the improvement of learning outcomes volleyball game approach to teaching terminal Elementary School fourth grade students Ngaliyan 03 . This study is an action research ( action research) because of research done to solve the problem of learning in the classroom . Data collected by field observation . The data analysis technique used is descriptive qualitative aspects which includes psychomotor , cognitive , and affective student . In the first cycle the average value reached 75.5 class that meets both criteria and completeness of student learning as many as 18 students ( 50.0 % ) , while incomplete as many as 18 students or 50 % . In the second cycle the average value reached 91.2 classes that meet the criteria very well and mastery learning students by 31 ( 86.1 % ) while the students did not complete as many as 5 or 13.9 % . Based on the above results , concluded that the game terminal Teaching to improve learning outcomes Volleyball . Therefore, teachers are advised to use the game Penjasorkes terminal as an alternative learning Teaching volleyball in elementary school .